2001
DOI: 10.1892/0891-6640(2001)015<0374:trodae>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Clostridium difficile and Enterotoxigenic Clostridium perfringens in Diarrhea in Dogs

Abstract: In this prospective study, feces of dogs with diarrhea were compared with feces of normal dogs for the presence of Clostridium difficile, C difficile toxins A and B, C perfringens, and C perfringens enterotoxin (CPE). C difficile toxins A, B, or both were present in feces of 18 of 87 (21%) dogs with diarrhea and 4 of 55 (7%) normal dogs (P 0.03), whereas CPE was present in the feces of 24 of 87 (28%) dogs with diarrhea and 3 of 55 (5%) normal dogs (P 0.01). C difficile was isolated from 2 of 87 (2%) dogs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
113
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 19 publications
9
113
5
Order By: Relevance
“…Consequently, it is safer for public health to consider C. difficile as potentially zoonotic (Arroyo et al, 2005;Weese et al, 2010). C. perfringens can be isolated from more than 80% of diarrheic and non-diarrheic dogs (Weese et al, 2001), whereas it is found more rarely in healthy cats and the isolation rates range between 43 and 63% (Marks et al, 2011). C. Perfringens Enterotoxin (CPE) is found in 34% of diarrheic dogs (Weese et al, 2001).…”
Section: Clostridium Sppmentioning
confidence: 99%
“…Consequently, it is safer for public health to consider C. difficile as potentially zoonotic (Arroyo et al, 2005;Weese et al, 2010). C. perfringens can be isolated from more than 80% of diarrheic and non-diarrheic dogs (Weese et al, 2001), whereas it is found more rarely in healthy cats and the isolation rates range between 43 and 63% (Marks et al, 2011). C. Perfringens Enterotoxin (CPE) is found in 34% of diarrheic dogs (Weese et al, 2001).…”
Section: Clostridium Sppmentioning
confidence: 99%
“…While signs of disease could range from mild self-limiting diarrhoea to chronic or fatal diarrhoea (Berry and Levett 1986), the relevance of the bacterium in small veterinary clinics is still uncertain (Weese 2011;Busch et al 2014). Different other studies have associated the presence of C. difficile in faeces with diarrhoea in dogs and cats (Weese et al 2001a;2001b;Weese and Armstrong 2003;Koene et al 2012;Wetterwik et al 2013). However, dogs can also be healthy carriers of C. difficile strains belonging to human epidemic PCR-ribotypes (Schneeberg et al 2012;Silva et al 2013b;Spigaglia et al 2015), with a high colonisation in the first period of live (Perrin et al 1993;Á lvarez-Pérez et al 2015).…”
mentioning
confidence: 98%
“…Necrosis and autolysis of mammalian cells present very similar morphological appearances, which can cause difficulties in assessment 10. Because all types of C. perfringens can normally inhabit the intestines of most animals, cultures of this microorganism from the intestinal contents of these animals has no diagnostic value, especially not cultures taken post mortem 11, 12, 13, 14. So far, no studies on the macroscopic appearance or on histologic changes performed intra vitam in dogs with HGE exist.…”
mentioning
confidence: 99%
“…However, C. perfringens can be cultured from the fecal specimens of more than 80% of diarrheic and nondiarrheic dogs, and CPE can also be detected in up to 14% of nondiarrheic, healthy dogs 11, 1515, 16, 17.…”
mentioning
confidence: 99%